Efektifitas Ekstrak Daun Pepaya Dalam Menunjang Keberhasilan Penetasan Telur Ikan Bandeng (Chanos chanos Forskall) - Teuku Fadlon Haser; Suri Purnama Febri; Muhammad Saleh Nurdin (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2018)
The availability of of milk fish fries has been becoming the inbitor in supporting milk fish production. Herbal ingredients such as papaya leaf’s extract can be an alternative to improve the success rate of hatchings and reduce fry abnormalities. The research aimed to examine the effectivity of papaya leaf’s extract in increasing hatching rate, and reducing the rate of abnormalities in milkfish fries. The treatment consists of six level concentration of papaya leaf’s extract which includes 2, 4, 6, 10, 20 and 25 ml. The research resulted in the highest success rate and the lowest abnormalities occur to the tratment with 4 ml papaya leaf’s extract (89, 94±1, 61 % dan 6, 54±2, 47 %). Therefore, papaya leaf extraction can significantly help to improve the success rate and minimize milk fish fries abnormality. Keyword: milkfish, papaya leaf’s extract, hatching rates, abnormalities.